Anne Frank's diary : the graphic adaptation - Folman, Ari; Frank, Anne, 1929-1945 (Pantheon Books, 2018)
Presents a graphic novel adaptation of "Anne Frank<U+0092>s Diary" that presents the journal of a Jewish girl in her early teens who describes both the joys and torments of daily life, as well as typical adolescent thoughts, throughout the two years spent in hiding with her family during the Nazi occupation of Holland.